ESR DATING EVIDENCE FOR EARLY MAN AT A LOWER PALAEOLITHIC CAVE-SITE IN THE NORTHERN CAUCASUS AS DERIVED FROM TERRESTRIAL MOLLUSC SHELLS - Molodkov A. (My University, 2001)
Eight terrestrial shell samples from recent excavations at Treugolnaya (Triangular) Cave (Northern Caucasus) were analysed by electron spin resonance (ESR) to produce a chronology for the most ancient Acheulian-bearing layers of the cave-site. The lifetime of the 2.0012 centre used for dating is about 3x108 at 5°C that allows to date the multi-level sequence of the cave-site at least in the range of the last one million years. The dating results obtained suggest that the first (from the bottom) archaeological layer, 7a, is likely to be about 583,000a old, and the next, 5b, is some 393,000 a old. These layers can be correlated with oxygen isotope stages 15 and 11, respectively. The estimates obtained imply that man presumably reached the Northern Caucasus at least as early as the beginning of stage 15, i.e. much earlier than generally recognised. The leaving of the cave by ancient man due to development of glacial environment during the subsequent stage(s) can probably be linked with the penetration of man to the southern areas of the East European Plain.
Keywords: ESR dating